ANALISIS KUALITAS PELAYANAN DAN KINERJA PENGEMUDI DENGAN KEPUASAN PENGGUNA MIKROTRANS JAK LINGKO DI DAERAH KHUSUS IBUKOTA (DKI) JAKARTA - Humairi, Kultsum Al; Nurcahyanto, Herbasuki; Marom, Aufarul (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
ABSTRACTImproving service quality and driver performance is needed to meet user satisfaction. Satisfaction is the level of a person's feelings after comparing the perceived service and performance with expectations. This study aims to determine the relationship between service quality, driver performance and user satisfaction of mikrotrans Jak Lingko in DKI Jakarta. This study uses a quantitative research approach with a total sample of 270 respondents who use mikrotrans Jak Lingko in DKI Jakarta. Based on this research, the results of the hypothesis test of the relationship between service quality and user satisfaction indicate a moderate and significant level of relationship and can be accepted, as evidenced by the results of the Kendall Tau correlation coefficient is 0.534, then Z-count 13.07> Z-table (5%) 1.96 and the percentage contribution of 28.5%. Hypothesis test results of the relationship between driver performance and user satisfaction indicate a moderate and significant level of relationship and can be accepted, as evidenced by the results of the Kendall Tau correlation coefficient is 0.514, then Z-count 12.58> Z-table (5%) 1.96 and the percentage contribution was 26.4%. Hypothesis test results of the relationship between service quality and driver performance with user satisfaction show a significant and acceptable relationship, as evidenced by the results of the Kendall tau concordance correlation coefficient, which is 0.814, then Chi-Square count> Chi Square table (5%) is 440.059> 5,991. with a contribution percentage of 66.2%. The three variables of this study have an average in the category of satisfied or good, although some indicators in these variables still show a score below the average. Suggestions that can be given for the constraints in these indicators are that the manager should be able to provide knowledge and take action against drivers to continue to improve service quality and driver performance of mikrotrans Jak Lingko in DKI Jakarta.